2006
DOI: 10.2214/ajr.04.1346
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Ablation Therapy of Hepatocellular Carcinoma Using Multitined Expandable Electrodes: Comparison of Subcapsular and Nonsubcapsular Tumors

Abstract: The rates of local tumor progression and complications for radiofrequency ablation using multitined expandable electrodes for subcapsular hepatocellular carcinomas were comparable to those for nonsubcapsular hepatocellular carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…The reason for the differences with our study is that they routinely used artificial pleural effusion for cases with tumors abutting the diaphragm or artificial ascites in cases when tumors abutted the gastrointestinal tract. In addition, our results for the local tumor progression rate were contrary to recent studies using a control group by Kim et al (13), Cho et al (22), and Sartori et al (23). Kim et al reported no significant difference in the local tumor progression rate between subcapsular HCCs and nonsubcapsular HCCs.…”
Section: Discussioncontrasting
confidence: 99%
“…The reason for the differences with our study is that they routinely used artificial pleural effusion for cases with tumors abutting the diaphragm or artificial ascites in cases when tumors abutted the gastrointestinal tract. In addition, our results for the local tumor progression rate were contrary to recent studies using a control group by Kim et al (13), Cho et al (22), and Sartori et al (23). Kim et al reported no significant difference in the local tumor progression rate between subcapsular HCCs and nonsubcapsular HCCs.…”
Section: Discussioncontrasting
confidence: 99%
“…The local recurrence rate of HCC, after segmental TACE, reported in prior studies has been around 30% (9). RF ablation therapy has been previously used primarily for the treatment of small nodular HCC tumors (16, 18-22). The local recurrence rate of small HCCs after RF ablation has been reported to be around 10-20% (16, 18-22).…”
Section: Discussionmentioning
confidence: 99%
“…RF ablation therapy has been previously used primarily for the treatment of small nodular HCC tumors (16, 18-22). The local recurrence rate of small HCCs after RF ablation has been reported to be around 10-20% (16, 18-22). Therefore, the 11.1% estimated 3-year local recurrence rate in Group IA can be regarded as acceptably low.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of risk factors for local tumor progression have been proposed in different studies, with controversial results [11][12][13][14][15][16][17][18]. Several independent risk factors for local tumor progression proposed in the previous investigations related to the geometry of the ablation zone and liver anatomy including lack of peritumoral ablative margin, heat sink effect of contiguous vessels, and subcapsular location.…”
Section: Patient Populationmentioning
confidence: 99%